2021
DOI: 10.1186/s12936-021-03914-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high frequency of MAD20 allelic variants of Plasmodium falciparum merozoite surface protein 1 gene from Adama and its surroundings, Oromia, Ethiopia

Abstract: Background One of the major challenges in developing an effective vaccine against asexual stages of Plasmodium falciparum is genetic polymorphism within parasite population. Understanding the genetic polymorphism like block 2 region of merozoite surface protein-1 (msp-1) gene of P. falciparum enlighten mechanisms underlining disease pathology, identification of the parasite clone profile from the isolates, transmission intensity and potential deficiencies of the ongoing malaria control and elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…The predominance of the MAD 20 for msp1 and the FC27 allelic family for msp2 among P. falciparum isolates was consistent with previous studies done in countries; Myanmar [ 34 ], Vietnam [ 35 ], Indonesia [ 36 ], that showed MAD 20 predominance and Pakistan [ 37 , 38 ], and Malaysia [ 39 ] that reported FC27 of msp2 dominance; The predominance of the MAD 20 for msp1 and the FC27 allelic family for msp2 were reported in other parts of Africa; North Central Nigeria [ 40 ], Equatorial Guinea [ 41 ], and Northwest Ethiopia [ 42 ]. Although this corroborates previous studies from Ethiopia finding similar patterns with the predominance of MAD 20 [ 43 ] and FC27 [ 44 , 45 ]. Predominance of MAD 20 of msp1 and 3D7/IC1 of msp2 in other reports had shown the predominance of K1 of msp1 and 3D7/IC1 of msp2 in southwestern Ethiopia [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…The predominance of the MAD 20 for msp1 and the FC27 allelic family for msp2 among P. falciparum isolates was consistent with previous studies done in countries; Myanmar [ 34 ], Vietnam [ 35 ], Indonesia [ 36 ], that showed MAD 20 predominance and Pakistan [ 37 , 38 ], and Malaysia [ 39 ] that reported FC27 of msp2 dominance; The predominance of the MAD 20 for msp1 and the FC27 allelic family for msp2 were reported in other parts of Africa; North Central Nigeria [ 40 ], Equatorial Guinea [ 41 ], and Northwest Ethiopia [ 42 ]. Although this corroborates previous studies from Ethiopia finding similar patterns with the predominance of MAD 20 [ 43 ] and FC27 [ 44 , 45 ]. Predominance of MAD 20 of msp1 and 3D7/IC1 of msp2 in other reports had shown the predominance of K1 of msp1 and 3D7/IC1 of msp2 in southwestern Ethiopia [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…It also revealed that the RO33 allelic family of msp1 was the most prevalent while a similar frequency was observed for both msp2 allelic families (3D7 and FC27). Studies carried out to assess the association between the distribution of msp1 allelic families and malaria status (asymptomatic and symptomatic) revealed different observations [44][45][46]. However, the RO33 allelic family was frequently reported in asymptomatic malaria cases [47].…”
Section: Discussionmentioning
confidence: 99%
“…The areas are characterized by low altitude (< 2000 m above sea level), heavy rainfall pattern from June to August followed by major transmission of malaria from September to December and short rains of February and March contributing for minor malaria transmission from April to May [ 18 ]. Geographical location of the study areas in Great Rift Valley, at low altitude, with rainfall pattern and average annual temperature of 16–32 °C make the areas favorable environments for breeding of Anopheles mosquitoes, of which Anopheles arabiensis is the major malaria vector [ 19 ]. Both P. falciparum and P. vivax co-exist in the area as it is common in different parts of the country.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmodium falciparum genomic DNA was extracted from dried blood spot (DBS) by Chelex extraction method as described elsewhere [ 19 ]. Extracted DNA was transferred into 0.5 ml tubes and stored at − 20 °C until further use.…”
Section: Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation